Peripheral versus central venous blood sampling does not influence the assessment of platelet activation in cirrhosis. (18th August 2022) - Brusilovskaya, Ksenia; Simbrunner, Benedikt; Lee, Silvia; Eichelberger, Beate; Bauer, David; Zinober, Kerstin; Schwabl, Philipp; Mandorfer, Mattias; Panzer, Simon; Reiberger, Thomas; Gremmel, Thomas
Abstract: Cirrhotic patients have an increased risk of bleeding and thromboembolic events, with platelets being involved as key players in both situations. The impact of peripheral versus central blood sampling on platelet activation remains unclear. In 33 cirrhotic patients, we thus analyzed platelet function in peripheral (P) and central (C) blood samples. Platelet surface expression of P -selectin, activated glycoprotein (GP) IIb/IIIa, and leukocyte-platelet aggregate formation were measured by flow cytometry in response to different agonists: thrombin receptor-activating peptide-6, adenosine diphosphate, collagen-related peptide (CrP), epinephrine, AYPGKF, Pam3CSK4, and lipopolysaccharide. Unstimulated platelet surface expression of P -selectin ( p = .850) and activated GPIIb/IIIa ( p = .625) were similar in peripheral and central blood samples. Stimulation with various agonists yielded similar results of platelet surface expression of P -selectin and activated GPIIb/IIIa in peripheral and central samples, except for CrP-inducible expression of activated GPIIb/IIIa (median fluorescence intensity, MFI in P: 7.61 [0.00–24.66] vs. C: 4.12 [0.00–19.04], p < .001). The formation of leukocyte-platelet aggregate was similar in central and peripheral blood samples, both unstimulated and after stimulation with all above-mentioned agonists. In conclusion, peripheral vs. central venous blood sampling does not influence the assessment of platelet activation by flow cytometry in cirrhosis. Abbreviations: ACLD : advanced chronic liver disease; ADP : adenosine diphosphate; ALD : alcoholic liver disease; AYPGKF : PAR-4 agonist AYPGKF; CrP : collagen related protein; EPI : epinephrine; FACS : fluorescence-activated cell sorting; GP : glycoprotein; HVPG : hepatic venous pressure gradient; IQR : interquartile range; LPS : lipopolysaccharide; LSM : liver stiffness measurement; MFI : median fluorescence intensity; NAFLD : nonalcoholic fatty liver disease; PAM : lipopeptide Pam3CSK4; PAR : protease-activated receptor; PBS : phosphate-buffered saline; PH : portal hypertension; TIPS: transjugular intrahepatic portosystemic stent shunt; TLR : toll-like receptor; TRAP-6 : thrombin receptor-activator peptide-6; vWF : von Willebrand factor